Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai Pada Dinas Sosial Provinsi Gorontalo - Arlin Mokedo; Melizubaida Mahmud; Sudirman Sudirman (State University of Gorontalo, 2023)
The study aimed to measure the effect of supervision on work discipline at the Social Agency of Gorontalo Province. This study was conducted using a quantitative approach, with a total of 47 respondents. The main instrument used during the data collection was a questionnaire. The data were than analyzed and tested with a simple regressions using the SPSS 2020. The results of the study showed that there was an effect of supervision an employee work discipline at the Social Agency of Gorontalo Province. The effect of supervision was 67,5 %, while the remaining 32,5% was affected by other variables.